2018
DOI: 10.1007/s00132-018-3536-5
|View full text |Cite
|
Sign up to set email alerts
|

Realignment surgery in adult spinal deformity

Abstract: Although surgical techniques pertaining to adult spinal deformity (ASD) have advanced over the last decade, proximal junctional kyphosis (PJK) is still a complication following surgery for ASD that continues to significantly challenge clinicians. This article aimed to report on the prevalence of PJK as well as enhance understanding of surgically modifiable and non-modifiable risk factors of PJK to guide management of this postoperative complication of ASD. As the understanding of the pathogenesis as well as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Moreover, spinal alignment is a unique anatomical feature, which allows the maintenance of a neutral upright posture with minimum energy expenditure [8]. Other researchers reported that older adults with spinal deformity have an impaired perception of upright vertical alignment that worsens with age-related impairment of proprioceptive and vibratory input from the lower extremities [9]. Correct posture allows one to retain a postural balance and limits movement in relation to the support plane, ensuring postural stability with minimum muscle involvement [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, spinal alignment is a unique anatomical feature, which allows the maintenance of a neutral upright posture with minimum energy expenditure [8]. Other researchers reported that older adults with spinal deformity have an impaired perception of upright vertical alignment that worsens with age-related impairment of proprioceptive and vibratory input from the lower extremities [9]. Correct posture allows one to retain a postural balance and limits movement in relation to the support plane, ensuring postural stability with minimum muscle involvement [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the initial Cobb angle measurements were made from T1 to T10; this might not be consistent with the measurements made in the literature or clinically, which are typically from superior end plate of T1 or T4 to the inferior end plate of T9 or T12. 63,46 Third, for our data, the lumbar and cervical segments of the reference spine geometry in standing posture was obtained by normalization of a generic thoracolumbar model and not from imaging and hence is not fully subject specific. Fourth, the validation of estimated spine geometry is performed only on the thoracic spine due to limitations in availability of full spine data in all the postures of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors of junctional kyphosis such as sagittal malalignment, 9 greater curvature correction, 9 , 10 , 11 , 12 and low bone mineral density, 11 , 13 have been reported in patients with adult spinal deformity, however, patients with LPTK were usually excluded due to specific pathogenesis. 10 , 14 , 15 The characteristics and risk factors of junctional kyphosis in patients with LPTK after long segmental instrumented fusion surgery are still unclear.…”
Section: Introductionmentioning
confidence: 99%